Human Face Recognition Using Wavelet Network - Zeyad, Dr. Tarik (Al-Khwarizmi Engineering Journal, 2017)
This paper presents a study of wavelet self-organizing maps (WSOM) for face recognition. The WSOM is a feed forward network that estimates optimized wavelet based for the discrete wavelet transform (DWT) on the basis of the distribution of the input data, where wavelet basis transforms are used as activation function.